2020
DOI: 10.1039/d0nr04886k
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular antibiotics: a strategy for conversion of broad-spectrum to narrow-spectrum antibiotics forStaphylococcus aureus

Abstract: The propensity of broad-spectrum antibiotics to indiscriminately kill both pathogenic and beneficial bacteria has a profound impact on the spread of resistance across multiple bacterial species. Alternative approaches that narrow...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…We have specifically shown that the H-bonding interaction among the attached functional groups influences the internal order of the self-assembled nanostructures and consequently the thermodynamic landscape of biomolecular adsorption. Further studies involving variation in the π-system and/or nature of the H-bonding group are underway with the broad objective to explore π-amphiphiles as supramolecular biomaterials. …”
Section: Discussionmentioning
confidence: 99%
“…We have specifically shown that the H-bonding interaction among the attached functional groups influences the internal order of the self-assembled nanostructures and consequently the thermodynamic landscape of biomolecular adsorption. Further studies involving variation in the π-system and/or nature of the H-bonding group are underway with the broad objective to explore π-amphiphiles as supramolecular biomaterials. …”
Section: Discussionmentioning
confidence: 99%
“…80 The ANAs underwent a stable/collapsed transition when exposed to SplB, and Ag + released from the collapsed ANAs exhibited biocidal activity to MRSA. Other enzymes such as glutamyl endonuclease (V8 enzyme), 81 type IV collagenases, 82 and β-lactamases 83 have also been reported as triggers for antibiotic release. In summary, these enzyme-responsive platforms achieved on-demand antibiotics release and demonstrated good antibacterial efficacy at the infection site.…”
Section: Biomaterials Sciencementioning
confidence: 99%
“…139 In aqueous solutions, these dendrimers containing penta(ethylene glycol) units as the hydrophilic moiety and decyl chain as hydrophobic moiety were found to form micelle-like aggregates within nanometer range. 140,141 Temperature-sensitivity due to the presence of ethylene glycol units were evaluated in different dendrimer generations. 142 A generation-dependent temperature-sensitivity was observed, due to the aggregation size and cooperativity when PEG moieties were tethered together in self-assembled dendrons (Fig.…”
Section: Impact Of Molecular Structures On ''Facially Amphiphilic'' D...mentioning
confidence: 99%